Behçet's disease diagnosed after acute HIV infection: viral replication activating underlying autoimmunity?. (May 2015) - Roscoe, Clay; Kinney, Rebecca; Gilles, Ryan; Blue, Sky
Behçet's disease is an autoimmune systemic vasculitis that can occur after exposure to infectious agents. Behçet's disease also has been associated with HIV infection, including de novo development of this condition during chronic HIV infection and resolution of Behçet's disease symptoms following initiation of antiretroviral therapy. We describe a patient who presented with systemic vasculitis with skin and mucous membrane ulcerations in the setting of acute HIV infection, who was eventually diagnosed with Behçet's disease, demonstrating a possible link between acute HIV infection, immune activation and development of autoimmunity.